Hypothesis: A Role for Fragile X Mental Retardation Protein in Mediating and Relieving MicroRNA-Guided Translational Repression?. (1st August 2006) - Plante, Isabelle; Provost, Patrick
Abstract : MicroRNA (miRNA)-guided messenger RNA (mRNA) translational repression is believed to be mediated by effector miRNA-containing ribonucleoprotein (miRNP) complexes harboring fragile X mental retardation protein (FMRP). Recent studies documented the nucleic acid chaperone properties of FMRP and characterized its role and importance in RNA silencing in mammalian cells. We propose a model in which FMRP could facilitate miRNA assembly on target mRNAs in a process involving recognition of G quartet structures. Functioning within a duplex miRNP, FMRP may also mediate mRNA targeting through a strand exchange mechanism, in which the miRNA * of the duplex is swapped for the mRNA. Furthermore, FMRP may contribute to the relief of miRNA-guided mRNA repression through a reverse strand exchange reaction, possibly initiated by a specific cellular signal, that would liberate the mRNA for translation. Suboptimal utilization of miRNAs may thus account for some of themolecular defects in patients with the fragile X syndrome.